A Novel Differential Predict Model Based on Matrix-Assisted Laser Ionization Time-of-Flight Mass Spectrometry and Serum Ferritin for Acute Graft-versus-Host Disease. (30th September 2013) - Zhang, Chun-yan; Wang, Shu-hong; Huang, Wen-rong; Guo, Guang-hong; Zhang, Zhu-hong; Mou, Wen-jun; Yu, Li; Tian, Ya-Ping
Abstract : Clinical diagnosis of acute graft-versus-host disease (aGVHD) mainly depends on clinical manifestation and tissue biopsies, leading to a delayed diagnosis and treatment for aGVHD patients when the early symptom is insignificant. Our objective was to investigate the possibility of prewarning the risk of aGVHD before and after allogeneic hematopoietic stem cell transplantation (allo-HSCT) by serum protein profiling combined with serum ferritin. The difference in polypeptide expression before and after transplantation had been compared by using CLINPROT technology, and serum ferritin levels have been analyzed simultaneously. Through combining serum ferritin and MS spectral data, the diagnosis sensitivity and specificity of our model for prewarning severe aGVHD (III~IV°aGVHD) before transplant all increased to 90.0%, while after transplant, the sensitivity and specificity are 78.3% and 86.4%. Our joint prewarning model could predict the risk of aGVHD, especially severe aGVHD before and after transplant, which also provides a reliable method to the continuous monitoring of the condition of patients.